AB0531 Decision to initiate immunosuppression in patients with primary sjogren's syndrome. (12th June 2018) - Daia-Iliescu, S.; Buzatu, C.; Gudu, T.; Zaharia, D.; Purice, C.; Borangiu, A.; Saulescu, I.; Groseanu, L.; Constantinescu, C.; Negru, M.M.; Vlad, V.; Bojinca, V.; et al.
Abstract : Background: There is limited data available (case series, small clinical trials and expert opinion) regarding the need to initiate immunosuppressive therapy in patients with primary Sjogren syndrome (pSS). Objectives: The aim of this study is to determine the factors that correlate with physician's decision to start immunosuppressive therapy in pSS patients. Methods: Subjects with pSS diagnosed according to the classification criteria in use at the time of their first presentation, were included in a monocentric cohort. A retrospective analysis was performed. The EULAR Sjogren's Syndrome Disease Activity Index (ESSDAI) at onset and Sjogren Syndrome Damage Index(SSDI) at the last evaluation were calculated. Treatment was given according to the physician's decision. Laboratory tests and Ultrasonography(US) of major salivary glands were performed in all cases. The data was analysed using Windows Excel/SPSS20.0. Results: Corticotherapy was prescribed in 26/30 cases (86.6%), mean duration 50.65 months. Immunomodulatory treatment with hydroxychloroquine was given in 26/30 cases (86.6%). Immunosuppressive treatment was required in 10/30 patients (33.3%)- azathioprine 7 (23.3%) cases, methotrexate 3 (10%)cases. The mean ESSDAI score was 6.83±SD 1.8. In 19 (63.3%)cases disease activity was moderate or high (ESSDAI >5). The mean damage score value (SSDI) was 3.1±SD1.2. There was a moderate correlation between the activity score ESSDAI and the damage score SDDI (r=0.41, p<0, 05). The physician's decision to start immunosuppression corelated significantly with the presence of hypergammaglobulinemia (r=0.4, p<0, 05). The duration of immunosuppressive treatment corelated moderately with specific Sjogren's US pattern of salivary glands (r=0.40, p<0.05). In contrast, immunosuppressive treatment duration did not corelate with the activity and damage scores (ESSDAI and SSDI). Conclusions: An important number of patients received corticotherapy, immunomodulatory agents and immunosuppressive therapy. The decision to initiate and maintain immunosuppressive therapy correlated with hypergammaglobulinemia and specific Sjogren's US changes. The damage score(SSDI) does not correlate with immunosuppressive therapy duration. References: [1] Rischmueller M, Tieu J, Lester S. Primary Sjögren's syndrome. Best Pract Res Clin Rheumatol2016Feb 30. [2] Seror R, Bootsma H, Saraux A, et al. Defining disease activity states and clinically meaningful improvement in primary Sjögren's syndrome with EULAR primary Sjögren's syndrome disease activity (ESSDAI) and patient-reported indexes (ESSPRI). Ann Rheum Dis2016. Disclosure of Interest: None declared